Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr) - Shattuck, Steven O. (Zootaxa, 2008)
The Australian members of the ant genus Aenictus are revised. Eight species were found to occur in Australia with three described as new (acerbus sp. n.., aratus Forel, diclops sp. n., hilli Clark, nesiotis Wheeler and Chapman, philiporum Wilson, prolixus sp. n. and turneri Forel). A. hilli is known only from males and its relationship to the remaining workerbased species is uncertain. Of the seven worker-based species, five are restricted to Australia, one is shared with Papua New Guinea and one is shared with Papua New Guinea and the Philippines. Aenictus aratus nesiotis Wheeler and Chapman is removed from synonymy with A. aratus and raised to full species, A. pachycerus impressus Karavaiev is newly synonymised with A. aratus and A. turneri is removed from synonymy with A. ceylonicus (Mayr). Additionally, the following changes are proposed for non-Australian species: A. aitkenii Forel is removed from synonymy with A. aratus, A. aratus asiatica Forel is removed from synonymy with A. aratus and synonymised with A. aitkenii, A. levior Karavaiev is removed from synonymy with A. aratus and raised to full species, A. orientalis (Karavaiev) is removed from synonymy with A. ceylonicus, A. papuanus Donisthorpe is removed from synonymy with A. ceylonicus and, together with A. similis Donisthorpe, is newly synonymised with A. orientalis. A lectotype is designated for A. impressus and a neotype for A. exiguus.